Knowledge management via smart library application: UTM experience - Talib, Anuar (2001)
The objective of the PSZ's Digital Library System is to make UTM's Library fully electronic, fulfilling the needs of its customers for current and fast information. This is in line with the Library's mission of providing and disseminating information and khowledge in the field of science and technology, fast and accurate; based on its professional expertise and employing information technology. In doing so, it will achieve its aim of being a reference centre of international standard.